Running performance in the heat is improved by similar magnitude with pre-exercise cold-water immersion and mid-exercise facial water spray - Stevens, C. J.; Kittel, A.; Sculley, D. V.; Callister, R.; Taylor, L.; Dascombe, B. J. (Journal of Sports Sciences, 2017)
This investigation compared the effects of external pre-cooling and mid-exercise cooling methods on running time trial performance and associated physiological responses. Nine trained male runners completed familiarisation and three randomised 5 km running time trials on a non-motorised treadmill in the heat (33°C). The trials included pre-cooling by cold-water immersion (CWI), mid-exercise cooling by intermittent facial water spray (SPRAY), and a control of no cooling (CON). Temperature, cardiorespiratory, muscular activation, and perceptual responses were measured as well as blood concentrations of lactate and prolactin. Performance time was significantly faster with CWI (24.5 ± 2.8 min; P = 0.01) and SPRAY (24.6 ± 3.3 min; P = 0.01) compared to CON (25.2 ± 3.2 min). Both cooling strategies significantly (P < 0.05) reduced forehead temperatures and thermal sensation, and increased muscle activation. Only pre-cooling significantly lowered rectal temperature both pre-exercise (by 0.5 ± 0.3°C; P < 0.01) and throughout exercise, and reduced sweat rate (P < 0.05). Both cooling strategies improved performance by a similar magnitude, and are ergogenic for athletes. The observed physiological changes suggest some involvement of central and psychophysiological mechanisms of performance improvement.